Age-Adjusted Endothelial Activation and Stress Index for Coronavirus Disease 2019 at Admission Is a Reliable Predictor for 28-Day Mortality in Hospitalized Patients With Coronavirus Disease 2019 - Pérez-García, Felipe; Bailén, Rebeca; Torres-Macho, Juan; Fernández-Rodríguez, Amanda; Jiménez-Sousa, Maria Ángeles; Jiménez, Eva; Pérez-Butragueño, Mario; Cuadros-González, Juan; Cadiñanos, Julen; García-García, Irene; Jiménez-González, María; Ryan, Pablo; et al. (Frontiers in Medicine, 2021)
Background: Endothelial Activation and Stress Index (EASIX) predict death in patients undergoing allogeneic hematopoietic stem cell transplantation who develop endothelial complications. Since COVID-19 patients also have coagulopathy and endotheliitis, we aimed to assess whether EASIX predicts death within 28 days in hospitalized COVID-19 patients. Methods: We performed a retrospective study on COVID-19 patients from two different cohorts (derivation (n=1200 patients) and validation (n=1830 patients)). The endpoint was death within 28 days. The main factors were EASIX [(LDH*creatinine)/thrombocytes] and aEASIX-COVID [EASIX*age], which were log2-transformed for analysis. Results: Log2-EASIX and log2-aEASIX-COVID were independently associated with an increased risk of death in both cohorts (p<0.001). Log2-aEASIX-COVID shows a good predictive performance for 28-day mortality both in the derivation cohort (area under the receiver-operating characteristic (AUROC)=0.827) and in the validation cohort (AUROC=0.820), with better predictive performance than log2-EASIX (p<0.001). For log2 aEASIX-COVID, patients with low/moderate risk (<6) had a 28-day mortality probability of 5.3% (95% confidence interval (95%CI)=4%–6.5%), high (6 – 7) of 17.2% (95%CI=14.7%–19.6%), and very high (>7) of 47.6% (95%CI=44.2%–50.9%). The cutoff of log2 aEASIX-COVID =6 showed a positive predictive value (PPV) of 31.7% and negative predictive value (NPV) of 94.7%, and log2 aEASIX-COVID =7 showed a PPV of 47.6% and NPV of 89.8%. Conclusion: Both EASIX and aEASIX-COVID were associated with death within 28 days in hospitalized COVID-19 patients. However, aEASIX-COVID had significantly better predictive performance than EASIX, particularly for discarding death. Thus, aEASIX-COVID could be a reliable predictor of death that could help to manage COVID-19 patients.